Exploring the Influence of ESG Transparency and Profitability Ratios on Firm Value in Emerging Markets - Santoso, Iqbal Pangestu (Universitas Pakuan, 2025)
This study aims to examine the impact of Environmental, Social, and Governance (ESG) disclosure and financial performance on firm value among companies in Indonesia’s food and beverage industry listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Using a quantitative research approach, the study employs panel data regression with purposive sampling across 24 companies, yielding a total of 96 observations. The independent variables consist of ESG disclosure and financial performance indicators, including Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Leverage, while firm value is measured using the Price to Book Value (PBV) ratio. Statistical analysis using the Fixed Effect Model (FEM) reveals that ESG disclosure and ROA have a positive and significant effect on firm value, whereas ROE exhibits a negative and significant relationship. Meanwhile, NPM and Leverage show no significant influence. The joint test results indicate that all independent variables simultaneously affect firm value with a coefficient of determination (R²) of 96.12%, suggesting that variations in firm value can be largely explained by ESG disclosure and financial performance metrics. These findings highlight the importance of sustainability reporting and efficient asset utilization in enhancing corporate valuation. The study contributes to the growing body of literature on sustainable finance by emphasizing the role of ESG transparency as a strategic factor influencing investor perception and firm competitiveness in emerging markets.